INVESTIGATION OF AGE-DIFFERENCES EFFECTON MASTERINGBASICUSINGAC-D PORTABLE SIMULATORFOR UNEMPLOYED COMMUNITY - Wiyono, Apri; Berman, Ega Taqwali; Rohendi, Dedi; Sumardi, Kamin; Mutaufiq, Mutaufiq; Sari, Dewi Puspita; Haikal, Haikal (Universitas Pendidikan Indonesia, 2020)
This research is conducted bythe problem of imbalance in the mastery of concepts, practices and activitiesof participants with a productive age range of 25-65 years in basic AC split system training. This happens because the method used is predominantly expository and visual media. Therefore, the trainer seeks to use the AC split media simulator in order to create an interesting learning atmosphere and increase the catchment and competence of participants. This study aims to determine the increase in learning outcomes, interests and motivation of participants in the productive age range 30 years and 30 yearsafter using the AC split learning instructional media on the AC split system training. The research method used was quasi-experimental, with variations in the object of research on 20 participants of tuna work in the village of Cigugur, Kuningan. Data collection techniques using questionnaires interest, motivation, pre-test and post-test. The results showed an increase in participants' learning outcomes as indicated by the average value of participant's interest in trainingactivities at productive age 30and 30 years with a score of 2.81 and 3.16, the category was quite good with an average N-Gain score of 55.89 and 36.26 medium category (30 â‰¤ G â‰¤ 70). The application of AC split simulator learning media also shows the learning motivation of participantsat the age of productive age range 30 years is greater than 30 years, amounting to 3.19: 3.08 with a fairly good category (Average score of 2.50-3.49). The distribution of N-Gain scores shows that the achievement of increased learning outcomes (training) for age 30 years tends to be higher on the scale of the medium category compared to the age range 30 years. The conclusion of this study, that the productive age range 30 years has a more significant increase in learning outcomes than the age range 30 years. by implementing the learning media of AC split simulator can increase the interest and motivation of participants in the basic AC split system training.